Star Trek : Season 1 DVD 5 - Roddenberry, Gene, 1921-1991; DeForest, Kelley, 1920-1999.; George Takei; James Doohan; Leonard Nimoy; Nichelle Nichols; Walter Koenig; William Shatner (USA Desilu Productions, 1966)
The adventures of the U.S.S. Enterprise, representing the United Federation of Planets on a five-year mission in outer space to explore new worlds, seek new life and new civilizations, and to boldly go where no man has gone before. The Enterprise is commanded by handsome and brash Captain James T. Kirk. His First Officer and best friend is Mr. Spock from the planet Vulcan, and Kirk's Medical Officer is Dr. McCoy. With its crew of approximately 430, the Enterprise battles aliens, megalomanical computers, time paradoxes, psychotic murderers, and even Genghis Khan!
Capt. Kirk and the crew of the Starship Enterprise explore space and defend the United Federation of Planets.
Languages : English, German, French, Spanish, Italian Subtitles : English, Turkish, German, French, Spanish, Italian, Russian, Czech, Dutch, Serbo-Croatian, Portuguese, Greek
Keywords: Adventure; SciFi -- Tv Series